Virtual Reality to Evaluate the Impact of Colorful Interventions and Nature Elements on Spontaneous Walking, Gaze, and Emotion - Batistatou, Adamantia; Vandeville, Florentin; Delevoye-Turrell, Yvonne N. (Frontiers in Virtual Reality, 2022)
Green environments are said to have a positive impact on spontaneous physical activity and well-being. However, high quality psychological measures in natural settings are difficult to collect. In the present study, we offer a detailed report on how virtual reality may provide a controlled environment for immersive user testing. Virtual Reality (VR) was here used to test the impact of colorful floor markings on the spontaneous speed of walking, gaze behaviour, as well as perceived changes in and physiological mesures of affective states. The reactions of 36 adult participants were evaluated in Grey and Green VR environments of an urban university campus. Results in VR revealed similar results than that reported in natural settings: participants walked slower and had higher heart rates in Green than in Grey urban settings, indicating more pleasurable experiences. VR results provided nevertheless more detailed description of user experience with the possibility to quantify changes in gaze strategy as a function of the presence or absence of color designs. Spontaneous walking was slower with colorful designs than without. Gaze behaviour presented longer fixation times with colorful designs than without. Finally, physiological responses indicated that mean heart rates were similar across environments and predicted the physical effort of the task. However, greater means in heart rates were observed in the environments presenting colorful designs, suggestion that colors may be a powerful tool to trigger alertness and pleasure in Grey urban cities. Virtual reality is reported here as an innovative method to quantify psychological experiences during free exploration during gait. Applicable to a broad range of research topics in the psychological sciences, explicit guidelines are made available to share computer code and data sets for further exploitation.